-4(x+y-z)+3(x-y+z)-2(-x+y+z)
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
-4x-4y+4z+3x-3y+3z+2x-2y-2z=x-9y-5z
Răspuns de
0
-4x-4y+4z+3(x-y+z)=
-4x-4y+4z+3x-3y+3z=
-x-4y+4z-3y+3z-2(-x+y+z)=
-x-7y+4z+3z-2(-x+y+z)=
-x-7y+7z-2(-x+y+z)=
-x-7y+7z+2x-2y-2z=
X-7y+7z-2y-2z=
X-9y+7z-2z=
X-9y+5z=
-4x-4y+4z+3x-3y+3z=
-x-4y+4z-3y+3z-2(-x+y+z)=
-x-7y+4z+3z-2(-x+y+z)=
-x-7y+7z-2(-x+y+z)=
-x-7y+7z+2x-2y-2z=
X-7y+7z-2y-2z=
X-9y+7z-2z=
X-9y+5z=
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă